Laryngo-Tracheal Displacement and Respiratory Distress in an Infant with Congenital Thymic Hyperplasia. (17th April 2011) - Wolff, Michael; Demirakca, Süha; Kilian, Anna Kristina; Schroten, Horst; Tenenbaum, Tobias
Abstract : Thymic hyperplasia is usually an asymptomatic condition observed in infancy. A five-week-old boy presented with respiratory distress and feeding disorder, in which chest X-ray and bronchoscopy revealed a strong laryngotracheal displacement. Sonography and MRI confirmed the diagnosis of a thymic hyperplasia. Corticosteroid therapy led to improvement of clinical symptoms. Thymic hyperplasia may lead to laryngo-tracheal displacement and respiratory distress in neonates and young children.